KEPEMIMPINAN Kepemimpinan Dengan Kepribadian Koleris - Fransius Kusmanto; Oci, Markus; Serenity, Fransisca Adelia (STT Internasional Harvest Tangerang, 2024)
A leader is a person who has the ability to influence a group of people in an effort to achieve organizational goals and other goals. Leaders are needed in a community. Without a leader, every community is likely to be in chaos. Good leadership is leadership that is able to put yourself in place and is able to see the opportunities that exist in every situation. Therefore it is very important to play a good role in any leadership. However, not everyone can be a good leader in every situation. A person's leadership can be seen how the person makes decisions. This is what sometimes becomes the subject of problems in leadership. There are leaders who find it difficult to make decisions that make their subordinates confused and even experience divisions. On the other side, the personality of a leader greatly influences in actions. The purpose in this paper is to find out the leadership style of a person with a choleric personality. The method used in this study is a qualitative method. The author uses this method to find out the overall choleric leadership style that is able to answer in a good leadership, supported by various existing sources such as books, articles and existing journals. The result of this study is that leadership with a choleric personality is excellent leadership to lead. With the style of the leader with a choleric personality is able to bring changes to the person he leads with the decisions made even in difficult situations.